Aksiologi Nilai Egaliter Budaya “Arek Suroboyo”. - Pratisto Tinarso; Supartiningsih Supartiningsih; Hardono Hadi (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2018)
This paper reveals the essence of egalitarian values ​​in the Arek Suroboyo culture. The egalitarian value of Arek Suroboyo's culture is a cultural value that has been possessed by the people of Surabaya since the era of the Ancient Mataram, when Surabaya was still named Hujunggaluh. Egalitarian values ​​grow as a form of cultural identity that is free and without caste. Axiologically the essence of Arek Suroboyo's egalitarian value is objective value and is an intrinsic value that has been lived by the people of Surabaya since the formation of the Surabaya community. The position of the Arek Suroboyo egalitarian value in the Max Scheler value hierarchy is spiritual value, because in the egalitarian value there is an appreciation of the dignity and position of humans who are equal to other humans. The limitation of Arek Suroboyo's egalitarian value is that it is still shackled in the communal culture of the Surabaya community. The egalitarian value of Arek Suroboyo contributes to strengthening local culture in Indonesia.